2012
DOI: 10.1557/jmr.2012.17
|View full text |Cite
|
Sign up to set email alerts
|

Confined crystallization in polymer nanolayered films: A review

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
123
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(126 citation statements)
references
References 93 publications
3
123
0
Order By: Relevance
“…In fact, it is found from many studies on the crystallization behavior that the crystallinity of block chains confined in nanolamellae increases sigmoidally with a finite induction time, indicating that the crystallization is virtually driven by a combined mechanism of heterogeneous nucleation and subsequent crystal growth. Because a comprehensive understanding of the detailed crystallization mechanism of homopolymers confined in nanolamellae is directly applicable to the surface crystallization of homopolymers [88][89][90][91][92] or crystallization within thin films [93][94][95][96][97][98], it is essential to examine the crystallization of homopolymers (and also block chains) confined in various nanolamellae.…”
Section: Nanolamellaementioning
confidence: 99%
“…In fact, it is found from many studies on the crystallization behavior that the crystallinity of block chains confined in nanolamellae increases sigmoidally with a finite induction time, indicating that the crystallization is virtually driven by a combined mechanism of heterogeneous nucleation and subsequent crystal growth. Because a comprehensive understanding of the detailed crystallization mechanism of homopolymers confined in nanolamellae is directly applicable to the surface crystallization of homopolymers [88][89][90][91][92] or crystallization within thin films [93][94][95][96][97][98], it is essential to examine the crystallization of homopolymers (and also block chains) confined in various nanolamellae.…”
Section: Nanolamellaementioning
confidence: 99%
“…In the past few years, the crystallization of polymers or polymer segments confined in ultrathin films (thickness <100 nm), miscible polymer blends and block copolymers has been widely studied for various systems. The unique crystallization kinetics, crystalline morphology, structure and melting process of polymers confined in such systems have been reviewed in several papers [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Baer et al [24][25][26][27][28][29][30][31][32][33][34][35] reported a miniaturized multilayer coextrusion technique. Such multilayer coextrusion represents an advanced polymer processing technique that combines two or more polymers in a layered configuration with controlled architecture.…”
Section: Introductionmentioning
confidence: 99%